Towards a maturity model for digital supply chains - Frauke Hellweg; Dustin Janhofer; Bernd Hellingrath (Logistics Research, 2023)
Emerging technologies like artificial intelligence, cloud computing, or big data play an important role in the digitalization of today's society, also impacting companies and their supply chains. However, the associated challenges are not only restricted to the technical dimension but include organizational or managerial issues as well. For companies, it is difficult to "get a grasp" of the complex digitalization processes regarding their supply chains. A maturity model provides a beneficial starting point to assess the current state and subsequently guide the further digitalization. Therefore, the paper aims to conduct the first steps necessary to develop a maturity model in the area of digital supply chains. As a result, a first draft of the "Digital Supply Chain Maturity Model" (DSCM²) is presented. The model development is accurately documented and follows a rigorous scientific methodology, grounded in in-depth literature reviews and expert interviews. First, the topic area is structured into four dimensions, namely business, organizational, process & method, and technological digitalization. Second, subdimensions, as well as maturity levels and their related maturity characteristics, are identified and described. Third, the model is evaluated from a practitioner's perspective in several iterations. The feedback from the experts is positive and minor changes are implemented. However, the model and the provided online self-assessment tool still have to be evaluated on a larger scale. Despite its limitations, this preliminary research can motivate future research and serve as a solid foundation for continued development of the model.
Keywords: 650; Digitalization; Supply Chain Management; Maturity Model Development; Literature Review; Semi-Structured Interviews